A cascade nanoreactor for enhancing sonodynamic therapy on colorectal cancer via synergistic ROS augment and autophagy blockage. (April 2023) - Zhang, Yujie; Zhao, Jingjie; Zhang, Lingmin; Zhao, Yuanru; Zhang, Yuanyuan; Cheng, Liangliang; Wang, Dan; Liu, Cui; Zhang, Mingxin; Fan, Kelong; Zhang, Mingzhen
Abstract: The ultrasound-triggered sonodynamic therapy (SDT) with high tissue penetration, high spatiotemporal selectivity, and non-invasive advantages represents an emerging approach to eradicating deep-seated solid tumors. However, the outcomes of SDT are typically hampered by the inefficient generation of reactive oxygen species (ROS) and the activation of protective autophagy. Here, to improve the antitumor efficiency of SDT on colorectal cancer, we rationally design a cascade nanoreactor by incorporating sonosensitizer Ce6 and autophagy inhibitor chloroquine into the homologous tumor cell membrane-modified hollow polydopamine nanocarrier that is pre-doped with platinum nanozymes (designated as CCP@HP@M). The cascade reactions of CCP@HP@M are evidenced by the results that HP exhibits superoxide dismutase-mimicking activity that converts O2 ·− to O2 and H2 O2, and platinum nanozymes further catalyze the excess H2 O2 to produce toxic ·OH and O2 . CCP@HP@M effectively accumulates in the tumor cells, resulting in a remarkably enhanced SDT efficiency for eliminating the tumor cells in vitro and in vivo . Under ultrasound irradiation, CCP@HP@M effectively alleviates the hypoxic condition, enhances ROS generation, and inhibits the protective autophagy pathway, which results in stimulating apoptosis and ferroptosis in vitro and in vivo . The RNA-seq analyses also confirmed apoptosis and ferroptosis pathways involved in the CCP@HP@M treatment. This cascade nanoreactor will provide a promising strategy for augmenting SDT eradication against tumors by modulation of ROS and autophagy. Graphical Abstract: Herein, we design a biomimetic cascade nanoreactor CCP@HP@M that is composed of Pt nanozyme-doped hollow polydopamine nanoreactor coated with the homologous cancer cell membrane and co-loaded with CQ and Ce6 to optimize SDT efficiency on colorectal cancer via ROS augment and autophagy inhibition strategies. ga1 Highlights: A cascade nanoreactor (SOD-CAT, SOD-POD) is constructed to enhance sonodynamic therapy by augmenting ROS production. CCP@HP@M treatment improves sonodynamic therapy via ROS augment and autophagy blockage. Under ultrasound irradiation, CCP@HP@M stimulates apoptosis and ferroptosis in vitro and in vivo . The RNA-seq analyses confirm apoptosis and ferroptosis pathways involved in the CCP@HP@M treatment.